Detection of beta-lactamase resistance genes in a hospital chlorinated wastewater treatment system - ȚUGUI, Claudia G.; VLĂDĂREANU, Ioana; BARICZ, Andreea; COMAN, Cristian (Studia Universitatis Babeș-Bolyai Biologia, 2015)
In this study, by amplification of several specific resistance genes we aimed at evaluating the presence of beta-lactamase resistance genes in the influent and effluent of a hospital chlorinated wastewater treatment system. Four types of beta-lactamase resistance genes (blaPER, blaVIM, blaNDM-1 and SHV) were detected in the influent water sample, two of which (blaVIM and SHV) being detected in the effluent as well. Our results indicate the reduced effectiveness of wastewater treatment, as several resistance genes can be found in the water discharged after the chlorination treatment.